A phylogenetic study of the Mongolian Tree Pipit (Anthus trivialis, Linnaeus, 1758) population based on mitochondrial DNA (mtDNA) genes - Tumendemberel, Ulziisaikhan; Byambadash, Sod-erdene; Sramko, Gabor; Batsukh, Tserendulam (Proceedings of the Mongolian Academy of Sciences, 2024)
Our aim was to identify nucleotide polymorphisms, assess their distribution in haplotype diversity, and construct a phylogenetic tree by analyzing mtDNA markers of the Mongolian Tree Pipits(Anthus trivialis). We conducted this study using partial gene sequencesof mitochondrial marker genes, such as COI, Cyt-b, D-loop, andND2,to determine the genetic diversity of Mongolian Tree Pipits. We successfully amplified 2307 bp of the mitochondrial DNA fragments, including 469bp of COI, 435bp of Cyt-b, 554bp of D-loop and 846bp of ND2 from total 27 individuals of Mongolian (21) and Hungarian (6) populations of Anthus trivialis.The Hd value wasthe highest for ND2 (0.96) as compared with the other gene fragments in all populations, whileit was 0.94 in the Mongolian population. Moreover, the nucleotide diversity (Pi) ranged from 0.00234 to 0.004 in all population, it was observed that the Pi was between 0.00183 and 0.00376 in the Mongolian population. The phylogenetic tree based on combined mtDNA sequences revealed two mean clades. The probability value of the node supporting the posterior between these clades is 0.65,which suggests an indicative support in relationship between the two clades. Furthermore, phylogenetic analysis showed that Mongolian Tree Pipits do share common genetic characteristics with other populations and do not form distinct clusters. Publisher correction: Author name Sabor Sramko was revised to Gabor Sramko dated on 2024-10-07.